Пошаговое объяснение:
3х²-10х+3 = 3х²- x - 9x + 3 = x*(3x - 1) - 3*(3x - 1) = (3x - 1)*(x - 3)
1) Исходя из того, что:
ax² + bx + c = a(x - x1)(x - x2),
где: x1, x2 - корни уравнения:
ax² + bx + c = 0
Решим уравнение:
3x² - 10x + 3 = 0
D = b² - 4ac = (-10)² - 4•3•3 = 100 - 36 = 64
x1 = (-b - √D)/2a = (10 - 8)/6 = 2/6 = 1/3
x2 = (-b + √D)/2a = (10 + 8)/6 = 18/6 = 3
Следовательно:
3x² - 10x + 3 = 3(x - ⅓)(x - 3) = (3x - 1)(x - 3)
2) 3x² - 10x + 3 = 3x² - 9x - x + 3 =
= (3x² - 9x) - (x - 3) = 3x(x - 3) - (x - 3) =
= (x - 3)(3x - 1)
Пошаговое объяснение:
3х²-10х+3 = 3х²- x - 9x + 3 = x*(3x - 1) - 3*(3x - 1) = (3x - 1)*(x - 3)
1) Исходя из того, что:
ax² + bx + c = a(x - x1)(x - x2),
где: x1, x2 - корни уравнения:
ax² + bx + c = 0
Решим уравнение:
3x² - 10x + 3 = 0
D = b² - 4ac = (-10)² - 4•3•3 = 100 - 36 = 64
x1 = (-b - √D)/2a = (10 - 8)/6 = 2/6 = 1/3
x2 = (-b + √D)/2a = (10 + 8)/6 = 18/6 = 3
Следовательно:
3x² - 10x + 3 = 3(x - ⅓)(x - 3) = (3x - 1)(x - 3)
2) 3x² - 10x + 3 = 3x² - 9x - x + 3 =
= (3x² - 9x) - (x - 3) = 3x(x - 3) - (x - 3) =
= (x - 3)(3x - 1)